Development and Assessment of a New Multichannel Electrocutaneous Device for Non-Invasive Somatosensory Stimulation for Magnetic Resonance Applications - Carolina Travassos; Alexandre Sayal; Paulo Fonte; Bruno Direito; Luis Lopes; Nuno Carolino; Sonia Afonso; Tania Lopes; Teresa Sousa; Miguel Castelo-Branco (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Non-invasive electrocutaneous stimulation, which applies an electrical current flowing through the skin’s surface to elicit a tactile percept, can be used in combination with functional magnetic resonance imaging (fMRI) to obtain somatotopic maps that illustrate the spatial patterns and functional organization of the primary somatosensory cortex (S1). However, accessibility to this technique, combined with fMRI, is limited, especially for applications requiring multiple stimulation channels. This study presents the development and assessment of a novel multichannel electrocutaneous stimulation device designed for non-invasive somatosensory stimulation of the upper limbs in human participants within a magnetic resonance (MR) environment. The current-controlled, voltage-limited stimulation device features 20 stimulation channels that can be individually configured to deliver various non-simultaneous combinations of personalized electrical pulses, tailored to the subject, stimulation site, and paradigm. It was designed with a modular assembly to ensure compatibility with the MR environment. The assessment of the device consisted of four stages. First, the feasibility of generating controllable electrical stimuli outside the MR environment was validated using an electrical circuit equivalent to the impedance of the human body and the electrode-skin interface. Subsequently, safety and compatibility were evaluated in a 3 Tesla Magnetom Prisma fit scanner using a phantom. Next, the device’s capacity to generate perceptible tactile sensations and user acceptability were assessed by testing the device on a single participant outside the MR environment. Finally, structural and functional data were acquired from three participants during a somatosensory stimulation experiment as a proof of concept to confirm the brain activity elicited by stimulation. These assessments confirmed the device’s capacity to generate controllable electrical stimuli both outside and in the MR environment, its compatibility and safety in this MR environment, and its effectiveness in eliciting brain activity in the expected brain areas without causing any discomfort to the participant. This study paves the way for future research on somatotopic mapping of S1 using this device.